A robust deterministic approach to node localisation using NLOS signal. (2018) - Mondal, Kaushik; Mandal, Partha Sarathi; Sinha, Bhabani P.
Localisation in an urban area is a challenging problem due to the blocking of line-of-sight (LOS) paths and the multipath effect arising out of reflection, scattering and diffraction of signals. We propose a technique to localise sensor nodes based on receiving reflected signals transmitted by anchor nodes. This method can calculate the position of a node by receiving non-line-of-sight (NLOS) signals in presence of range measurement error with better accuracy compared to existing works. We, however, assume that a signal is reflected at most once before reaching a node. While a network is growing, wrong position information may get assigned to some nodes by accident. According to our robust localisation in NLOS, an anchor can detect inconsistency of the wrong position information with the help of three reply signals from a particular node via different paths.